CD39 activities in the treated acupoints contributed to the analgesic mechanism of acupuncture on arthritis rats - Yu-Jia Li; Jie Lin; Si-Qi Tang; Wei-Min Zuo; Guang-Hong Ding; Xue-Yong Shen; Li-Na Wang (Purinergic Signalling, 2025)

Neuroprotection of exercise: P2X4R and P2X7R regulate BDNF actions - Bing-xin Sun; Ai-shi Peng; Pei-jie Liu; Min-jia Wang; Hai-li Ding; Yu-shi Hu; Liang Kang (Purinergic Signalling, 2023)
The neurotrophin brain-derived neurotrophic factor (BDNF), which acts as a transducer, is responsible for improving cerebral stroke, neuropathic pain, and depression. Exercise can alter extracellular nucleotide levels and purinergic receptors in central nervous system (CNS) structures. This inevitably activates or inhibits the expression of BDNF via purinergic receptors, particularly the P2X receptor (P2XR), to alleviate pathological progression. In addition, the significant involvement of sensitive P2X4R in mediating increased BDNF and p38-MAPK for intracerebral hemorrhage and pain hypersensitivity has been reported. Moreover, archetypal P2X7R blockade induces mouse antidepressant-like behavior and analgesia by BDNF release. This review summarizes BDNF-mediated neural effects via purinergic receptors, speculates that P2X4R and P2X7R could be priming molecules in exercise-mediated changes in BDNF, and provides strategies for the protective mechanism of exercise in neurogenic disease.

The real-time detection of acupuncture-induced extracellular ATP mobilization in acupoints and exploration of its role in acupuncture analgesia - Wei-Min Zuo; Yu-Jia Li; Kai-Yu Cui; Dan Shen; Di Zhang; Ya-Wen Zheng; Meng Huang; Yong Wu; Xue-Yong Shen; Li-Na Wang; Guang-Hong Ding (Purinergic Signalling, 2023)